EVALUASI PENERAPAN STANDAR PELAYANAN MINIMAL (SPM) PENDIDIKAN MENENGAH DI PROVINSI BANTEN - Subki Subki; Agus Sjafari; Arenawati Arenawati (Jurnal Kebijakan Pembangunan Daerah, 2022)
The application of the Minimum Service Standards (MSS) for secondary education is the focus of the Banten Provincial Government as an effort to implement the implementation of compulsory basic service affairs. This study discusses the evaluation of the implementation of the MSS for Secondary Education carried out by the Education and Culture Office of Banten Province with the CIPP public policy evaluation approach (Context, Input, Process, Product). This research is expected to provide input suggestions for the Banten Provincial Government in the Implementation of MSS. The research method used is a descriptive method with a qualitative approach. Results Based on the research, the application of the MSS for Secondary Education in Banten Province has not been optimal. In the context dimension, it shows that the Banten Provincial Government has integrated the content into the Banten Province RPJMD document for 2017-2022, the strategies needed to encourage and provide facilitation to education units in improving the National Education Standards (SNP) and efforts for educator certification strategies and mapping and improvement teachers so that the ratio of teachers to students at the SMA and SMK levels in Banten Province. In the Input dimension, the aspects of human resources and budget allocation are sufficient, however, it is necessary to form a MSS team for Secondary Education to improve understanding and accelerate the fulfillment of MSS for secondary education. In the Process dimension, the percentage of certified high school and vocational high school teachers in the Quality Improvement Program for Educators and Education Personnel is very low, below 50 percent due to the limited quota of participants for the Teacher Professional Education program from the Central Government. In product, the scope for fulfilling the SPM for Secondary Education in Banten Province has not yet been fulfilled. Keywords: Evaluation, Minimum Service Standards (MSS), secondary education, public policy.